(untitled) (Biological Sciences - PJSIR, 1995)
Karachi has been a fast growing city by any standards and planning could never keep the pace of construction. Engineering properties of the soils in various parts of the city have been studied to evaluate the foundation conditions. It is found that the soils of Karachi, in the northern part, are coarse grained, medium to coarse sand and sandy gravel, well graded and unimodel. The moisture content, bulk density and specific gravity are in the range where shallow foundations can safely be placed for medium sized civil projects, Shear strength of the soil has been tested in the field by an improvised penetration test and by pocket penetrometer at three feet depth. The results provide a useful guideline and it is believed that the standard test for penetration will corporate with the obtained results. The foundations in the southern part of the city, particularly in Defence Housing Society, require caution. The soil is finer in size, very poorly graded and recently deposited in tidal flats, creeks and swamps. Drainage conditions are poor and the problem of salinity and water logging is encountered in the area. More high-rise buildings are being built in this part of the city and each site deserves to be carefully examined for the foundation conditions including the seismic risk.